2023
DOI: 10.1186/s12913-022-08738-0
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of national health insurance enrolment among people at risk of statelessness in the Awutu Senya East Municipality and Gomoa East District of Ghana

Abstract: Background This paper investigates the factors influencing the decision to enrol in Ghana’s National Health Insurance Scheme (NHIS) among people at risk of statelessness, with emphasis on the individual's demographic and socioeconomic factors.  Methods The study used data from a cross-sectional household survey undertaken in the Awutu Senya East Municipality and Gomoa East District of Ghana's Central Region between March 9 and June 26, 2021, on hea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Studies from various countries have shown that certain populations, such as the unemployed or those in poverty, have a lower likelihood of enrolling in health insurance and may face higher out-of-pocket costs for healthcare. For example, a study in Ghana found that individuals aged 56 to 65 and without employment were less likely to enroll in health insurance, with nearly half of participants paying for membership out of pocket [21]. Similarly, in Korea, a large number of households subscribed to private health insurance, but very few received reimbursements for medical costs or services [22].…”
Section: Discussionmentioning
confidence: 99%
“…Studies from various countries have shown that certain populations, such as the unemployed or those in poverty, have a lower likelihood of enrolling in health insurance and may face higher out-of-pocket costs for healthcare. For example, a study in Ghana found that individuals aged 56 to 65 and without employment were less likely to enroll in health insurance, with nearly half of participants paying for membership out of pocket [21]. Similarly, in Korea, a large number of households subscribed to private health insurance, but very few received reimbursements for medical costs or services [22].…”
Section: Discussionmentioning
confidence: 99%
“…Studies among different sub-populations such as informal sector workers in Indonesia found those who experienced financial hardships to be 7.7 percentage points less likely to pay insurance premiums routinely [ 67 ]. On technological challenges, existing evidence in the literature shows the internet challenges as one of the operational barriers to health insurance coverage among older adults in Ghana [ 68 , 69 ]. The need for effective measures to address this challenge to promote UHC, particularly among older persons is a catalyst for achieving SDG 3.…”
Section: Discussionmentioning
confidence: 99%
“…Unemployment in low and middle-income Countries (LMICs) such as Ghana has been seen as a major contributory factor to migration especially among working class people [ 33 ]. Data indicates that more than 2 million Ghanaians representing 14.7% were unemployed by the 3rd quarter of 2023 with only about 12 million employed [ 34 ].…”
Section: Discussionmentioning
confidence: 99%